So, and if it is not congenital adrenal hyperplasia? Addressing an undiagnosed case of genital ambiguity - Reinaldo Luna de Omena Filho; Reginaldo José Petroli; Fernanda Caroline Soardi; Débora de Paula Michelatto; Taís Nitsch Mazzola; Helena Fabbri-Scallet; Maricilda Palandi de Mello; Susane Vasconcelos Zanotti; Ida Cristina Gubert; Isabella Monlleo (Italian Journal of Pediatrics, 2022)
Abstract Background The Congenital Adrenal Hyperplasia due to 21 hydroxylase deficiency is the most common cause of genital ambiguity in persons with XX sexual chromosomes. Genital ambiguity among persons with XY sexual chromosomes comprises diverse and rare etiologies. The deficiency of 17-beta-hydroxysteroid dehydrogenase type 3 enzyme (HSD17B3) is a rare autosomal recessive disorder due to functionally altered variants of the HSD17B3 gene. In this disorder/difference of sex development, the conversion of androstenedione into testosterone is impaired. The appearance of external genitalia of 46,XY individuals varies from typically male to almost female. Case presentation We report on a child presenting severe ambiguous genitalia. Due to access constraints, specialized care did not start until the child was 10 months old. Parents are consanguineous and were born in an area of high isonymy that is a cluster for rare recessive diseases. A new homozygous missense variant c.785G > T was found in exon 10 of the HSD17B3 gene. Conclusions Researchers-clinicians and researchers-researchers collaborative efforts to elucidate the genetic basis of this disease were critical since this etiologic investigation is not available through the public health system. This case exemplifies the families’ pilgrimage in cases of genital ambiguity due to a rare genetic condition. Recognizing the etiology was the baseline to provide information on prognosis and treatment options, and to shelter family and child doubts and hopes in order to better support their decisions.